Are We Able to Determine Differences in Outcomes Between Male and Female Servicemembers Undergoing Hip Arthroscopy? A Systematic Review. Issue 11 (16th November 2021) - Rhon, Daniel I.; Greenlee, Tina A.; Dickens, Jonathan F.; Wright, Alexis A.
Background: Female servicemembers sustain higher rates of lower extremity injuries as compared with their male counterparts. This can include intra-articular pathology in the hip. Female patients are considered to have worse outcomes after hip arthroscopy for femoroacetabular impingement and for hip labral repair. Purpose: To (1) compare published rates of hip arthroscopy between male and female military servicemembers and (2) determine if there are any sex-based differences in outcomes after hip arthroscopy in the military. Study Design: Systematic review; Level of evidence, 3. Methods: We reviewed the literature published from January 1, 2000, through December 31, 2020, to identify studies in which hip arthroscopy was performed in military personnel. Clinical trials and cohort studies were included. The proportion of women within each cohort was identified, and results of any between-sex analyses were reported. Results: Identified were 11 studies that met established criteria. Studies included 2481 patients, 970 (39.1%) of whom were women. Surgery occurred between January 1998 and March 2018. Despite women accounting for approximately 15% of the active-duty military force, they represented 39.1% (range, 25.7%-57.6%) of patients undergoing hip arthroscopy. In most cases, there were no differences in self-reported outcomes (pain, disability, and physical function), return to duty, or medical disability status based on sex. Conclusion: Women account for approximately 15% of the military, but they made up 40% of patients undergoing hip arthroscopy. Outcomes were not different between the sexes; however, definitive conclusions were limited by the heterogeneity of outcomes, missing data, lack of sex-specific subgroup analyses, and zero studies with sex differences as the primary outcome. A proper understanding of sex-specific outcomes after hip arthroscopy will require a paradigm shift in the design and reporting of trials in the military health system.